Pendampingan Tradisi Mequlhu Melalui Pendekatan Living Quran guna Meningkatkan Kesadaran Membaca Al-Quran - Karsidin; Ainung, Dwi Ulfahmi; Ningrum, Baiq Mustika; Adha, Idil; Adzah, Isti; Sari, Harlina Puspita; Alisyah, Nur (IAIN Kendari, 2025)
The Mequlhu tradition in the death ritual in Rapambinopaka Village, Lalonggasomeeto District is a practice of dhikr of the Al-Ikhlash letter using small stones or stone dhikr. This practice is an integration of local wisdom with the Quran in the midst of the social environment of the community. The practice of this tradition, through a living Quran approach with a group-based mentoring method that aims to increase awareness of reading the Quran and actualizing the values ​​of the Mequlhu tradition among members of the community. This mentoring is a form of education and counseling in understanding the meaning and spiritual practices contained in the ritual, as a form of respect for the bereaved family or the deceased and also as a means to strengthen brotherhood and bring to life the values ​​of the teachings of the Quran. The results of this mentoring show an increase in public awareness in reading the Quran, creating space for reflection and deep understanding of spirituality as well as local wisdom values ​​in society. In conclusion, through the living Quran approach in the Mequlhu tradition, it has succeeded in integrating traditional practices with the principles and values ​​contained in the Al-Quran which makes it a cultural identity that is relevant in a social context.